A Possible Role of Allatostatin C in Inhibiting Ecdysone Biosynthesis Revealed in the Mud Crab Scylla paramamosain - Liu, An; Shi, Wenyuan; Lin, Dongdong; Ye, Haihui (Frontiers in Marine Science, 2021)
C-type allatostatins (C-type ASTs) are a family of structurally related neuropeptides found in a wide range of insects and crustaceans. To date, the C-type allatostatin receptor in crustaceans has not been deorphaned, and little is known about its physiological functions. In this study, we aimed to functionally define a C-type ASTs receptor in the mud crab, Scylla paramamosian. We showed that C-type ASTs receptor can be activated by ScypaAST-C peptide in a dose-independent manner and by ScypaAST-CCC peptide in a dose-dependent manner with an IC50 value of 6.683 nM. Subsequently, in vivo and in vitro experiments were performed to investigate the potential roles of ScypaAST-C and ScypaAST-CCC peptides in the regulation of ecdysone (20E) and methyl farnesoate (MF) biosynthesis. The results indicated that ScypaAST-C inhibited biosynthesis of 20E in the Y-organ, whereas ScypaAST-CCC had no effect on the production of 20E. In addition, qRT-PCR showed that both ScypaAST-C and ScypaAST-CCC significantly decreased the level of expression of the MF biosynthetic enzyme gene in the mandibular organ, suggesting that the two neuropeptides have a negative effect on the MF biosynthesis in mandibular organs. In conclusion, this study provided new insight into the physiological roles of AST-C in inhibiting ecdysone biosynthesis. Furthermore, it was revealed that AST-C family peptides might inhibit MF biosynthesis in crustaceans.